ZBiotics ameliorates T2DM-induced histopathological damage in liver, kidney and adipose tissues by modulating the NOD-like receptor signaling in Wistar rats - Mohammed Esawie; Marwa Matboli; Mariam Sameh Bushra; Amany H. Hasanin; Eman Kamal Habib; Reham Hussein Mohamed; Hebatalla Said Ali (Diabetology & Metabolic Syndrome)
Abstract Probiotics serve as promising candidates in type 2 diabetes mellitus (T2DM) therapy. Not only they presumably reduce the T2DM prevalence, but also keep down its complications. In the present study, we explored the beneficial impact of ZBiotics, an engineered probiotic, on T2DM Wistar rats. In silico analysis was performed to construct a genetic-epigenetic network linked to STING-NOD pathway and autophagy signaling. Then, 30 Wistar rats were divided into 5 groups (each n = 6); normal group, diabetic model, B. subtilis, and ZBiotics treated rats at high and low doses. Experimental procedures were carried out including biochemical and histopathologic analyses. Samples were extracted from rats’ blood, liver, kidney and adipose tissues. At the molecular aspect, the molecular players, chosen by the in silico analysis, were assessed using 2–ΔΔCt to estimate their relative quantification. With immunohistochemistry, TNF-alpha and LC3B were assessed as reflectors for inflammation and autophagy respectively. ZBiotics was reported to ameliorate the T2DM-induced histological damage. Besides, it downregulated TNF-alpha and upregulated LC3B expression levels. At the biochemical aspect, ZBiotics corrected LDL-c and improved serum creatinine and CK-MB levels. Inflammation relevant genes have been downregulated regarding CHUK, NFKB1 and miR-611. Therefore, ZBiotics is speculated to operate by modulating the genetic-epigenetic network linked to inflammatory cGAS-STING and autophagy signaling. ZBiotics is recommended for clinical trials as a separate candidate or as an adjuvant to the conventional T2DM therapy.